Causal relationships between systemic inflammatory cytokines and adhesive capsulitis: a bidirectional Mendelian randomization study - Ouyang, Yi; Dai, Miaomiao (Frontiers in Immunology, 2024)
Background: Mounting evidence suggests a connection between inflammatory cytokines and adhesive capsulitis (AC). However, the specific systemic inflammatory cytokines contributing to this processAC have not been clearly identified. This study employeds Mendelian randomization (MR) to further investigateexplore the causal relationships between 41 inflammatory cytokines and AC. Methods: In this bidirectional, two-sample MR analysis, genetic variations associated with AC were derived from a comprehensive genome-wide association study (GWAS). The inflammatory cytokines data were sourced from a GWAS summary involving 8,293 healthy participants. The primary MR method employed was inverse variance weighting, supplemented by MR-Egger, weighted median, and MR-pleiotropy residual sum and outlier for sensitivity analysis. Heterogeneity was assessed using Cochrane's Q test, and the stability of MR results was were ensured throughvalidated using the leave-one-out method.Results: Elevated levels of interferon gamma-induced protein 10 (IP-10) (odds ratio (OR) = 1.086, 95% confidence interval (CI) = 1.002--1.178) and regulated on activation, normal T cell expressed and secreted (RANTES) (OR = 1.107, 95% CI = 1.026--1.195) weare linked to an augmented increased risk of AC risk. Higher Increased levels of stromal cell-derived factor-1 alpha (SDF-1α) (OR = 0.879, 95% CI = 0.793--0.974) and tumor necrosis factor-alpha (TNF-α) (OR = 0.911, 95% CI = 0.831--0.999) levels awere associated with a reduced AC risk. Moreover, genetically predicted AC manifests exhibited associations with elevated cCutaneous T -cell attracting (CTACK) levels (OR = 1.202, 95% CI = 1.007--1.435) and diminished levels of interleukin-17 (IL-17) (OR = 0.678, 95% CI = 0.518--0.888) and interleukin-5 (IL-5) (OR = 0.786, 95% CI = 0.654--0.944), as discerned confirmed through inverse-variance weighted (IVW) methods.Conclusions: Our The present study successfully establishes a causal association between genetically proxied circulating levels of IP-10, RANTES, SDF-1α, and TNF-α and the risk of AC. Additionally, AC contributes to an increase in CTACK and a decrease in IL-17 and IL-5. This significant finding not only enhances our the understanding of the pathogenesis of AC but also holds promise for the development of effective clinical management strategies.